2000
DOI: 10.1097/00004424-200001000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Tumor-Targeting MR Contrast Agent Using the High-Affinity Folate Receptor

Abstract: This new agent accumulates in tumors expressing hFR. These results do not differentiate between active and passive targeting mechanisms. Receptor-negative tumors suggest a mechanism other than a nonspecific blood pool effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 31 publications
2
85
0
1
Order By: Relevance
“…98 An alternative to polylysine vectors are nonlinear polycationic cascade polymers. 102 Also known as dendrimers, these polycations are spheroidal, can amplify the amount of therapeutic or diagnostic agent reaching the tumor cells, 103 and mediate higher transfection efficiency of therapeutic agents into cells than their linear counterparts. 102 Immune-mediated targeting of FRa-positive tumors, founded on the historical observation that antibodies are raised against FRa, 104 offer sophisticated strategies to deliver cytotoxic agents via bispecific antibody targeted T cell therapy (characterized by cytotoxic T lymphocyte-mediated tumor cell lysis), adoptive transfer of tumor-specific T lymphocytes (characterized by T cell activation and cytokine release), and immunocytokines (e.g., targeting IL-2/MOv19 fusion protein to FRa-expressing cells to activate migrating T cells).…”
Section: Exploitation Of Fra For Therapeutic and Diagnostic Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…98 An alternative to polylysine vectors are nonlinear polycationic cascade polymers. 102 Also known as dendrimers, these polycations are spheroidal, can amplify the amount of therapeutic or diagnostic agent reaching the tumor cells, 103 and mediate higher transfection efficiency of therapeutic agents into cells than their linear counterparts. 102 Immune-mediated targeting of FRa-positive tumors, founded on the historical observation that antibodies are raised against FRa, 104 offer sophisticated strategies to deliver cytotoxic agents via bispecific antibody targeted T cell therapy (characterized by cytotoxic T lymphocyte-mediated tumor cell lysis), adoptive transfer of tumor-specific T lymphocytes (characterized by T cell activation and cytokine release), and immunocytokines (e.g., targeting IL-2/MOv19 fusion protein to FRa-expressing cells to activate migrating T cells).…”
Section: Exploitation Of Fra For Therapeutic and Diagnostic Potentialmentioning
confidence: 99%
“…107 Magnetic resonance (MR) imaging contrast agents based on dendrimers conjugated to folic acid and targeted to FRa-positive tumor cells have also shown improved enhancement of MR images in mice. 103 These newer conjugates are capable of concentrating at pathologic sites as non-invasive probes for diagnostic imaging and do not suffer from problems associated with ligands such as antibodies, which among other factors, can be immunogenic and expensive to produce. 98 Finally, the sensitivity of GPI links to specific phospholipases, such as phospholipase C and D, which are abundant in plasma, may also provide a means to control FRa level at the cell surface 64 or to develop sensitive biomarker assays of the soluble protein for early detection, 66,108 as has recently been described for 2 folate-related disorders.…”
Section: Exploitation Of Fra For Therapeutic and Diagnostic Potentialmentioning
confidence: 99%
“…Indeed, Wiener and co-workers used Gd(DTPA) (diethylenetriamine-N,N,N',N'',N''-pentaacetic acid) dendrimers conjugated with folic acid for visualizing the folate receptor, which is overexpressed in many tumors. [9] The complex [Fe{Gd 2 L(H 2 O) 4 } 3 ] 4À contains six Gd III ions, each exhibiting high relaxivity, for a molecular mass of 3744 g mol À1 . Consequently, its efficiency by a unity mass is particularly high.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…There is a great deal of interest in enhancing the utility of these tools in medicine and research through the development of molecularly-targeted MRI contrast agents. One example might be a chimeric molecule comprised of a contrast agent tethered to a molecule capable of binding to a specific protein or other biomolecular target with high affinity and specificity [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For example, we previously reported that a peptide selected from a phage display library to bind the yeast Gal80 protein can be linked to GdDOTA to create a reagent capable of imaging Gal80 protein in vitro [18,19].…”
Section: Introductionmentioning
confidence: 99%